Management of Educational Financing in OMNI Elementary School Cibinong - Morisson, Buci; Widayati, Ani; Djunaedi, Atikah; Susanto, Umar Yeni; Purnamasari, Niken (FKIP Universitas Lampung, 2024)
This study investigates the management of educational financing at OMNI School Elementary in Cibinong, Bogor, emphasizing its vital role in supporting the continuity of the teaching and learning process. The research aims to evaluate the effectiveness of school fund utilization, financial reporting, and transparency in managing educational funds. Additionally, it identifies potential mismanagement issues and examines how these funds improve classroom learning quality. The findings offer deeper insights into more effective and efficient school fund management, positively impacting students' learning outcomes. This qualitative study adopts a single-case design focusing on the financial management of OMNI School Elementary. Data were gathered through documentation and interviews to analyze the financial management practices in the school. The results reveal no significant financial constraints at the institution. The allocated funds are efficiently used for various educational needs, reflecting proper allocation and effective utilization. OMNI School implements a robust accountability system, characterized by its commitment to transparency, such as publicly posting financial reports on the school noticeboard. This fosters an atmosphere of transparency and accountability, positively affecting the quality of classroom learning. Well-managed financial resources have enabled the provision of essential facilities, improving the overall educational experience. This study highlights the importance of accountability and transparency principles in achieving sustainable educational quality development.DOI: http://dx.doi.org/10.23960/E3J/v7.i2.190-201